Preparation method of antibacterial soft anti-powdering dust-free paper and disposable sanitary products

By combining chlorinated fatty alkyldimethylbenzyl ammonium chloride with polyamide epoxy chloride resin, an antibacterial soft powder-proof resin is formed, which solves the poor antibacterial effect and powder-free dust paper, and improves the antibacterial activity and softness of dust-free paper.

CN115897253BActive Publication Date: 2025-04-11FUJIAN HENGAN HLDG CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211663648.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-04-11
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

The existing antibacterial treatment methods of dust-free paper have problems such as poor antibacterial effect, weakening of the effect after combining quaternary ammonium salt with villi pulp, antagonism with hyperabsorbent resin, and re-seepage irritation of the skin.

Method used

The chlorinated fatty alkyl dimethyl tertiary amine and benzyl chloride were used to prepare chlorinated fatty alkyl dimethyl benzyl ammonium chloride, and combined with polyamide epoxy chlorohydrin resin to form an antibacterial soft powder-proof resin, sprayed on the surface of the velvet pulp and the ES fiber web, and the antibacterial activity was made by reinforcement by hot air.

Benefits of technology

The antibacterial activity of dust-free paper is achieved, powder loss is prevented and softness is improved, the antagonism of quaternary ammonium salts and highly absorbent resins is avoided, and the risk of reflux irritation is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115897253B_ABST
    Figure CN115897253B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing antibacterial, soft, and anti-powdering dust-free paper and disposable sanitary products. The method comprises: preparing chlorinated fatty alkyl dimethyl tertiary amine by reacting with benzyl chloride; preparing polyamide epichlorohydrin resin by using diethylenetriamine, adipic acid, and chlorinated epichlorohydrin as raw materials; adding chlorinated fatty alkyl dimethyl benzyl ammonium chloride to polyamide epichlorohydrin resin to prepare antibacterial, soft, and anti-powdering resin; spraying the prepared antibacterial, soft, and anti-powdering resin on the surface of fluff pulp and ES fiber web, and consolidating with hot air to obtain dust-free paper with antibacterial activity. In the present invention, chlorine replaces the electron-withdrawing group so that the cationic charge of the ammonium group on the polyamide epichlorohydrin resin is greater than the cationic charge of the ammonium group of fatty alkyl dimethyl benzyl ammonium chloride, and the ammonium group of the polyamide epichlorohydrin resin is adsorbed on the fluff pulp fiber, while the ammonium group of fatty alkyl dimethyl benzyl ammonium chloride is away from the fluff pulp fiber, so that the ammonium group is exposed and exerts antibacterial activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing antibacterial, soft, anti-powdering dust-free paper and a disposable sanitary product using the dust-free paper. Background Art

[0002] Antibacterial dust-free paper used in diapers and sanitary napkins can effectively inhibit the growth of microorganisms after use, thereby reducing the occurrence of allergies. At present, the antibacterial treatment of dust-free paper generally adopts non-dissolving inorganic system or quaternary ammonium salt organic system. Compared with the organic quaternary ammonium salt system, the inorganic silver and zinc oxide system has the problem of poor antibacterial effect.

[0003] If the quaternary ammonium salt organic system is adsorbed by the fluff pulp, the antibacterial effect will be greatly weakened. Once it is freed, it will have an antagonistic effect with the anionic super absorbent resin, resulting in a decrease in the performance of the super absorbent resin. At the same time, it will penetrate back to the surface of the sanitary product and come into direct contact with the skin, causing irritation. Summary of the invention

[0004] In order to overcome the above-mentioned defects, the object of the present invention is to provide a method for preparing antibacterial, soft, anti-powdering dust-free paper and disposable sanitary products using the dust-free paper.

[0005] To achieve the above object, the method for preparing the antibacterial soft anti-powdering dust-free paper of the present invention comprises the following steps:

[0006] The chlorinated fatty alkyl dimethyl tertiary amine is reacted with benzyl chloride to prepare chlorinated fatty alkyl dimethyl benzyl ammonium chloride;

[0007] Polyamide epichlorohydrin resin is prepared using diethylenetriamine, adipic acid and epichlorohydrin chloride as raw materials;

[0008] The prepared chlorinated fatty alkyl dimethyl benzyl ammonium chloride is added into the prepared polyamide epichlorohydrin resin to prepare an antibacterial, soft and anti-powdering resin;

[0009] The prepared antibacterial, soft and anti-powdering resin is sprayed on the surface of the combed fluff pulp and ES fiber web, and then reinforced with hot air to obtain dust-free paper with antibacterial activity.

[0010] To achieve the above object, the disposable sanitary product of the present invention comprises a surface layer, an absorption layer and a bottom layer, wherein the absorption layer is provided with dust-free paper obtained by the preparation method of the antibacterial, soft and anti-powdering dust-free paper.

[0011] Furthermore, the surface layer includes an upper layer of PE / PP hot air non-woven fabric and a lower layer of PE / PET hot air non-woven fabric, and the upper and lower layers of hot air non-woven fabric are formed by ultrasonic welding.

[0012] Furthermore, the upper and lower layers of hot air nonwoven fabric are three-dimensional perforated structures with an opening rate of 4-8% and a hole density of 5-8 per cm 2 , the holes in the upper and lower layers are staggered.

[0013] Furthermore, the absorption layer comprises, from top to bottom, an upper layer of dust-free paper, an absorption resin and a lower layer of dust-free paper.

[0014] Furthermore, the absorption layer includes a C-shaped wrapping paper surrounded by dust-free paper, and an upper layer of dust-free paper, an absorbent resin and a lower layer of dust-free paper are arranged from top to bottom in the wrapping paper; the opening of the wrapping paper corresponds to the surface layer.

[0015] Furthermore, the opening is 1 / 3 of the effective width of the disposable sanitary product.

[0016] Furthermore, the disposable sanitary product also includes a surface layer, and the surface layer is made of soft skin-friendly non-woven fabric; the preparation method of the non-woven fabric includes the following steps:

[0017] preparing metal-doped fullerene masterbatch;

[0018] Preparation of fullerene-grafted softener containing sulfonate anion;

[0019] The prepared fullerene-grafted softener containing sulfonate anions is added into the ES fiber hydrophilic oil agent;

[0020] ES fibers are prepared by spinning process using metal-doped fullerene masterbatch and ES fiber hydrophilic oil agent;

[0021] The ES fibers were used to prepare nonwoven fabrics.

[0022] Furthermore, the step of preparing the metal-doped fullerene masterbatch comprises:

[0023] Metal-doped fullerenes were prepared by arc discharge method;

[0024] The metal-doped fullerene, polyethylene resin and dispersant are uniformly mixed at high speed, and melt-extruded and granulated in a twin-screw extruder to obtain the metal-doped fullerene masterbatch.

[0025] The further step of preparing the fullerene-grafted softener containing sulfonate anions comprises:

[0026] In the C60 or C70 fullerene benzene solution, KOH solution and tetrabutylammonium hydroxide as a phase transfer catalyst are added, and then H 2 O 2After reacting for 12 hours at room temperature, the aqueous solution changes from colorless to brown-yellow, and the benzene solution changes from purple to colorless. Phase separation is performed using a separatory funnel to obtain a dark brown hydroxylated fullerene solution, which is then centrifuged and purified by adding methanol, and then dried in vacuum to obtain hydroxylated fullerene;

[0027] The hydroxylated fullerene is reacted with (9Z)-9-octadecenoic acid, aminosulfonic acid and diethyl sulfate to prepare a fullerene-grafted softener containing sulfonate anions.

[0028] The present invention designs a self-crosslinking network structure containing the positive charge of the quaternary ammonium salt group. The chlorine-substituted electron-withdrawing group makes the cationic charge of the ammonium group on the polyamide epichlorohydrin resin greater than the cationic charge of the ammonium group of the fatty alkyl dimethyl benzyl ammonium chloride. The ammonium group of the polyamide epichlorohydrin resin is adsorbed on the fluff pulp fiber, while the ammonium group of the fatty alkyl dimethyl benzyl ammonium chloride is away from the fluff pulp fiber, so that the ammonium group is exposed and exerts antibacterial activity. At the same time, due to the characteristics of the self-crosslinking network structure, it has multiple binding sites, which can ensure close binding with the fluff pulp without falling off. The combination of the resin and the fluff pulp can fix the fluff pulp, thereby preventing powder from falling off. At the same time, the long-chain alkyl group has good softness and can improve the softness of dust-free paper. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the reaction formula for preparing polyamide epichlorohydrin resin in the embodiment of the present invention.

[0030] Figure 2 This is the reaction formula for preparing the antibacterial, soft and anti-powdering resin in the embodiment of the present invention. DETAILED DESCRIPTION

[0031] Since the fluff pulp surface cannot be 100% grafted, some quaternary ammonium salts are not fixed on the fluff pulp surface. Once free, they will affect the performance of the super absorbent resin (antagonism between cations and acrylic anions). At the same time, after grafting, the quaternary ammonium salt cations will be adsorbed on the fiber surface, and the ammonium groups cannot be exposed, thereby affecting the antibacterial activity. The present invention aims to overcome the above defects, design a self-crosslinking network structure resin containing quaternary ammonium salt groups, and combine it with fluff pulp to achieve a non-dissolution antibacterial effect.

[0032] As an embodiment of the present invention, the following steps are included: Figure 1 , Figure 2 As shown:

[0033] The chlorinated fatty alkyl dimethyl tertiary amine is reacted with benzyl chloride to prepare chlorinated fatty alkyl dimethyl benzyl ammonium chloride;

[0034] Polyamide epichlorohydrin resin is prepared using diethylenetriamine, adipic acid and epichlorohydrin chloride as raw materials;

[0035] The prepared chlorinated fatty alkyl dimethyl benzyl ammonium chloride is added into the prepared polyamide epichlorohydrin resin to prepare an antibacterial, soft and anti-powdering resin;

[0036] The prepared antibacterial, soft and anti-powdering resin is sprayed on the surface of the combed fluff pulp and ES fiber web, and then reinforced with hot air to obtain dust-free paper with antibacterial activity.

[0037] Example 1

[0038] 1 mol of chlorinated fatty alkyl dimethyl tertiary amine is reacted with 1 mol of benzyl chloride to prepare chlorinated fatty alkyl dimethyl benzyl ammonium chloride;

[0039] 1.02 mol of diethylenetriamine and 1 mol of adipic acid were reacted to form prepolymer PA, and 1 mol of chloro-epichlorohydrin was used as raw material to prepare polyamide epichlorohydrin resin with a solid content of 12.5%;

[0040] The prepared chlorinated fatty alkyl dimethyl benzyl ammonium chloride is added to the prepared polyamide epichlorohydrin resin to prepare an antibacterial, soft and anti-powdering resin;

[0041] The prepared antibacterial, soft and anti-powdering resin was sprayed on the surface of the combed fluff pulp and ES fiber web (the spraying amount was 10 g / M 2 ), and then hot air reinforced to produce dust-free paper with antibacterial activity.

[0042] In the present invention, the chlorine-substituted electron-withdrawing group makes the cationic charge of the ammonium group on the polyamide epichlorohydrin resin greater than the cationic charge of the fatty alkyl dimethyl benzyl ammonium chloride. The ammonium group of the polyamide epichlorohydrin resin is adsorbed on the fluff pulp fiber, while the ammonium group of the fatty alkyl dimethyl benzyl ammonium chloride is away from the fluff pulp fiber, so that the ammonium group is exposed and exerts antibacterial activity.

[0043] Conventional dust-free paper has poor adhesion between fluff pulp, so when used in the production of sanitary napkins and diapers, powder will fall off, and the machine needs to be cleaned frequently, affecting production efficiency, otherwise the product will be dirty. However, due to the self-crosslinking network structure of the present invention, it has multiple binding sites, which can ensure close bonding with the fluff pulp without falling off. The combination of resin and fluff pulp can fix the fluff pulp, thereby preventing powder from falling off. At the same time, the long-chain alkyl group has good softness, which can improve the softness of dust-free paper.

[0044] test

[0045] 1. Quaternary ammonium salt dissolution test: Take 5g of antibacterial dust-free paper treated with antibacterial agents, cut it into pieces and put it into 100mL of deionized water for ultrasonic treatment for 10 minutes, filter it, and test the nitrogen content in the filtrate according to "HJ 616-2012 Determination of total nitrogen in water quality - alkaline potassium persulfate digestion ultraviolet spectrophotometry". The blank sample is dust-free paper without antibacterial treatment, and the control sample is dust-free paper directly sprayed with benzalkonium chloride.

[0046] Blank Experimental Sample Control Nitrogen concentration / mg / L 0.2 0.3 9.8

[0047] 2. Determination of the bactericidal performance of dust-free paper: Test the bactericidal performance of dust-free paper according to C3 in GB 15979

[0048]

[0049]

[0050] 3. Test of diaper permeability: Test according to Appendix A of GB / T 28004.1-2021 Diapers Part 1: Baby Diapers

[0051]

[0052] 4. Powder loss rate test: Test according to Appendix B of GB / T 20808-2022 Paper Towels

[0053] Blank Experimental Sample Control Powder loss rate / % 1.8 0.3 1.5

[0054] 5. Softness test: Tested in accordance with GB / T 8942-2016 Determination of paper softness

[0055]

[0056] As an embodiment of the present invention, the disposable sanitary product of the present invention can be a sanitary napkin or a diaper. The disposable sanitary product of the present invention comprises a surface layer, an absorption layer and a bottom layer, wherein the absorption layer is provided with dust-free paper prepared by the preparation method of the antibacterial soft anti-powdering dust-free paper.

[0057] The above-mentioned absorption layer can be designed as needed, for example: a sandwich structure including an upper layer of dust-free paper, an absorbent resin and a lower layer of dust-free paper from top to bottom. It can also be a edging structure made of dust-free paper: the dust-free paper is surrounded by a C-shaped edging paper, and an upper layer of dust-free paper, an absorbent resin and a lower layer of dust-free paper are arranged from top to bottom in the edging paper; the opening of the edging paper corresponds to the surface layer; the opening is 1 / 3 of the effective width of the disposable sanitary product. It also includes a design with more layers, such as a structure in which an upper layer of dust-free paper, an upper layer of absorbent resin, a non-woven fabric, a lower layer of absorbent resin and a lower layer of dust-free paper are arranged from top to bottom in the edging paper. Of course, a multi-layer dust-free paper design can also be used as needed.

[0058] As another embodiment of the present invention, the surface layer comprises an upper layer of PE / PP hot air nonwoven fabric and a lower layer of PE / PET hot air nonwoven fabric, and the upper and lower layers of hot air nonwoven fabric are formed by ultrasonic welding. The upper and lower layers of hot air nonwoven fabric are three-dimensional perforated structures, with an opening rate of 4-8% and a hole density of 5-8 per cm 2 , the holes in the upper and lower layers are staggered.

[0059] As another embodiment of the present invention, the disposable sanitary product further comprises a surface layer, wherein the surface layer is made of a skin-care soft non-woven fabric; the preparation method of the skin-care soft non-woven fabric comprises the following steps:

[0060] Preparation of metal-doped fullerene masterbatch: metal-doped fullerene, polyethylene resin, and dispersant (polyethylene wax and stearic acid) are uniformly mixed at high speed, and melt-extruded and granulated in a twin-screw extruder to obtain metal-doped fullerene masterbatch.

[0061] Preparation of fullerene grafted softener containing sulfonate anion; Fullerene (C60, C70) is hydroxylated. In C60 or C70 benzene solution, KOH solution is added, tetrabutylammonium hydroxide is used as a phase transfer catalyst, and then H2O2 is added to react at room temperature for 12 hours. The aqueous solution changes from colorless to brownish yellow, and the benzene solution changes from purple to colorless. Phase separation is performed using a separatory funnel to obtain a dark brown hydroxylated fullerene solution, methanol is added for centrifugal purification, and vacuum drying is performed to obtain the hydroxylated fullerene.

[0062] The fullerene-grafted sulfonate anion softener is prepared by reacting hydroxylated fullerene with (9Z)-9-octadecenoic acid, aminosulfonic acid and diethyl sulfate to prepare a fullerene-grafted sulfonate anion-containing softener.

[0063] Preparation of ES fiber oil: Fullerene-grafted quaternized anionic softener is added to conventional ES fiber hydrophilic oil and applied to ES fiber.

[0064] ES fibers are prepared by spinning process using metal-doped fullerene masterbatch and ES fiber hydrophilic oil agent.

[0065] Example 2

[0066] Preparation of metal-doped fullerene masterbatch: 18 parts of metal-doped fullerene, 80 parts of polyethylene resin, and 2 parts of dispersant (polyethylene wax and stearic acid) are uniformly mixed at high speed, and melt-extruded and granulated in a twin-screw extruder to obtain metal-doped fullerene masterbatch.

[0067] Preparation of fullerene grafted softener containing sulfonate anion: Fullerene (C60, C70) was hydroxylated. In 100 mL of 2 mg / mL C60 or C70 benzene solution, 2 mL of 1 mol / L KOH solution was added, 8 drops of 10% tetrabutylammonium hydroxide as a phase transfer catalyst, and then 3 mL of 30% H 2 O 2 After reacting for 12 hours at room temperature, the aqueous solution changes from colorless to brown-yellow, and the benzene solution changes from purple to colorless. Phase separation is performed using a separatory funnel to obtain a dark brown hydroxylated fullerene solution, which is then centrifuged and purified by adding methanol, and then dried in vacuum to obtain hydroxylated fullerene.

[0068] The fullerene grafted sulfonate anion softener is prepared by reacting 1 part of hydroxylated fullerene with 1 part of (9Z)-9-octadecenoic acid, 1 part of aminosulfonic acid and 1 part of diethyl sulfate to prepare the fullerene grafted sulfonate anion-containing softener.

[0069] Preparation of ES fiber oil: 10% fullerene grafted quaternary ammonium anion softener was added to conventional ES fiber hydrophilic oil and applied to ES fiber.

[0070] ES fibers are prepared by spinning process using metal-doped fullerene masterbatch and ES fiber hydrophilic oil agent.

[0071] In the above method, the sulfonate anion group is adsorbed on the fiber surface of the positively charged metal-doped fullerene masterbatch, and the long carbon chain in the softener interacts with the fiber through van der Waals force, thereby solving the problem of fullerene adhesion on the fiber.

[0072] The two fullerenes in different addition forms are used to synergistically eliminate free radicals to achieve skin care functions, thereby reducing skin problems. The fullerenes in the fiber spinning oil absorb the free radicals of the skin and transfer them to the fullerene fiber masterbatch to achieve a long-term free radical elimination effect.

[0073] As an embodiment of the present invention, the disposable sanitary product of the present invention can be a sanitary napkin or a diaper. The disposable sanitary product at least comprises a surface nonwoven fabric, and the disposable sanitary product uses the nonwoven fabric prepared by the preparation method of the skin-care soft nonwoven fabric of the above embodiment.

[0074] Test method:

[0075] 1. Diaper pretreatment: Test according to the permeability test method of code L in Appendix A of GB / T 28004.1-2022

[0076] 2. A quantitative DPPH load was fixed on artificial skin to simulate free radicals on human skin. The artificial skin was attached to the surface of the diaper that had been tested for permeability performance and was placed in a dark place at 25°C for 30 minutes.

[0077] 3. Place the artificial skin after the test into an excess of vitamin C solution for full reaction, and calculate the DPPH clearance rate based on the remaining vitamin C in the test solution.

[0078] The test plan and results are shown in the table below.

[0079]

[0080]

[0081] Through the above test comparison, it can be seen that the DPPH elimination rate in the solution of adding the fullerene-grafted quaternary ammonium anion softener of the present invention into the fiber spinning oil + ES fiber containing fullerene masterbatch reaches 99%.

[0082] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0083] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing antibacterial soft anti-powdering dust-free paper, characterized in that: The method comprises the following steps: The chlorinated fatty alkyl dimethyl tertiary amine is reacted with benzyl chloride to prepare chlorinated fatty alkyl dimethyl benzyl ammonium chloride; Polyamide epichlorohydrin resin is prepared using diethylenetriamine, adipic acid and epichlorohydrin chloride as raw materials; The prepared chlorinated fatty alkyl dimethyl benzyl ammonium chloride is added into the prepared polyamide epichlorohydrin resin to prepare an antibacterial, soft and anti-powdering resin; The prepared antibacterial, soft and anti-powdering resin is sprayed on the surface of the combed fluff pulp and ES fiber web, and then reinforced with hot air to obtain dust-free paper with antibacterial activity.

2. A disposable sanitary product, comprising a surface layer, an absorbent layer and a bottom layer, characterized in that: in, The absorption layer is provided with dust-free paper prepared by the method for preparing antibacterial, soft, anti-powdering dust-free paper as claimed in claim 1.

3. The disposable sanitary product according to claim 2, characterized in that: The surface layer comprises an upper layer of PE / PP hot air non-woven fabric and a lower layer of PE / PET hot air non-woven fabric, and the upper and lower layers of hot air non-woven fabric are formed by ultrasonic welding.

4. The disposable sanitary product according to claim 3, characterized in that: The upper and lower layers of hot air nonwoven fabric are three-dimensional perforated structures with an opening rate of 4-8% and a hole density of 5-8 per cm 2 , the holes in the upper and lower layers are staggered.

5. The disposable sanitary product according to claim 2, characterized in that: The absorption layer comprises, from top to bottom, an upper layer of dust-free paper, an absorption resin and a lower layer of dust-free paper.

6. The disposable sanitary product according to claim 2, characterized in that: The absorption layer includes a C-shaped wrapping paper surrounded by dust-free paper, in which an upper layer of dust-free paper, an absorbent resin and a lower layer of dust-free paper are arranged from top to bottom; the opening of the wrapping paper corresponds to the surface layer.

Citation Information

Patent Citations

  • Wet Paper Strengthening Agent And Paper Containing Wet Paper Strengthening Agent

    CN103966902A

  • Product containing epichlorohydrin, its preparation and its use in various applications

    CN105153068A